2019
DOI: 10.1634/theoncologist.2019-0241
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Chemotherapy Toxicity and Death in Older Adults with Colon Cancer: Results of MOST Study

Abstract: Purpose Older patients with colon cancer (CC) are vulnerable to chemotherapy toxicity and death. Establishing simple scores specific for patients with CC to predict severe chemotoxicity or early death is needed to select the best treatment strategy. Subjects, Materials, and Methods This prospective multicenter study included patients aged ≥70 years with CC receiving adjuvant or first‐line metastatic chemotherapy. Frailty markers (nutrition, physical activity, energy, mobility, strength), comprehensive geriatri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 42 publications
3
49
0
1
Order By: Relevance
“…Almost half of the studies [16, 34-36, 40-43, 45, 48-50, 55, 60, 62, 63, 66-68, 75, 78, 80, 82, 84, 86] reported on patients with various types of cancer. Thirty studies [33, 37-39, 44, 46, 47, 51-54, 56-59, 61, 65, 69-74, 76, 77, 79, 81, 83, 85, 87] focused on a specific type, with lung [52-54, 56, 81, 87] and colorectal cancer [37,39,44,46,51,65,69,76,77] as the most common types. Fifteen studies [33, 39, 44, 52-58, 60, 76, 81, 84, 87] [16, 38, 39, 43, 45, 50, 58, 59, 61, 63, 67, 68, 73-77, 81, 85, 86] the MNA-SF, and in 5 studies [33][34][35][36][37] a stepwise approach that considered both forms was used.…”
Section: Study and Patient Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost half of the studies [16, 34-36, 40-43, 45, 48-50, 55, 60, 62, 63, 66-68, 75, 78, 80, 82, 84, 86] reported on patients with various types of cancer. Thirty studies [33, 37-39, 44, 46, 47, 51-54, 56-59, 61, 65, 69-74, 76, 77, 79, 81, 83, 85, 87] focused on a specific type, with lung [52-54, 56, 81, 87] and colorectal cancer [37,39,44,46,51,65,69,76,77] as the most common types. Fifteen studies [33, 39, 44, 52-58, 60, 76, 81, 84, 87] [16, 38, 39, 43, 45, 50, 58, 59, 61, 63, 67, 68, 73-77, 81, 85, 86] the MNA-SF, and in 5 studies [33][34][35][36][37] a stepwise approach that considered both forms was used.…”
Section: Study and Patient Characteristicsmentioning
confidence: 99%
“…Nine studies investigated the association between baseline MNA and treatment toxicity [46,48,58,69,73,76,80,81,84] (Table 2, Additional file table 3d). In only 1 of these studies [48], a significant higher risk for nonhematologic toxicity was shown for patients with (risk of) malnutrition compared to well-nourished patients, while for other toxicity outcomes (hematologic, acute radiotherapy or significant toxicity) MNA-result was not predictive [46,73,80] or not investigated in adjusted analyses [69,76,81,84].…”
Section: Adverse Treatment Outcomesmentioning
confidence: 99%
“…In the chemotoxicity scores Cancer and Aging Research Group (CARG) and CRASH, age was included only in the CARG score [33,35]. In a recent predicting death score in older adults with colon cancer, age >82 years was selected as prognostic factor [36]. But older age alone should not be decisive for oncological treatment decision making; patient decisions and high-risk factors such as functional status (IADL or ADL), malnutrition, and cognitive or mobility impairment are more important [37].…”
Section: Discussionmentioning
confidence: 99%
“…The CRASH and CARG tools can be extrapolated and useful for the determination of frailty and the risk of toxicity of chemotherapy in mCRC; although their validation studies did not specifically address for these cases, they included many patients in whom the cancer origin was intestinal (12% and 27% respectively). Recently, a model has been proposed to predict the risk of developing toxicity and early death in chemotherapy-treated colon cancer patients [ 36 ]. However, this model has not yet been validated.…”
Section: Frailty In Elderly Patients With Metastatic Crcmentioning
confidence: 99%
“…GA can be a very useful tool to achieve this objective. Moreover, there are other tools that can predict the risk of developing severe chemotherapy toxicity [ 32 , 33 , 36 , 90 , 91 ]. Conducting the GA is very useful not only before starting the treatment but also during or at the end of the chemotherapy in order to evaluate the impact of the treatment on health.…”
Section: Global Interpretationmentioning
confidence: 99%